Attitude towards what is said in the academic scientific environment. Alternative for postgraduate training (Islas, 2023)
Introduction: This work addresses a highly relevant topic in the current context: the need to advance in the generalization and didactic application of attitudinal contents to make timely transcultural contributions to postgraduate education.Methods: Drawing on Bakhtinian conceptualizations of the voice of the other, this research adopts the theoretical and methodological premises of dialogism and transcultural polyphony, situated within the qualitative paradigm to study its object through educational ethnography.Results: It presents the guidelines of a didactic alternative for handling attitudes towards what is said in the academic-scientific environment of the Master's program in Linguistic Studies of Spanish as a Foreign Language at the Faculty of Spanish for Non-Spanish Speakers, University of Havana. The transcultural polyphony of voices in that context is described.Conclusions: The lack of a voice in relation to what is said also operates in this academic-scientific sphere: attitudes and positions are presented that overshadow or exclude those who do not belong to the same personal or social, cultural, academic, and professional interest circles.
Keywords: alternative; attitude; modality; voices; dialogism; transcultural poliphony